Does player age influence match physical performance? A longitudinal four-season analysis in Spanish soccer LaLiga - Garcia-Calvo, T.; Huertas, F.; Ponce-Bordón, J. C.; Del Campo, R. L.; Resta, R.; Ballester, R. (Biology of Sport, 2023)
This study aims to analyse the evolution of match running performance in relation to the age distribution of professional soccer players using a large-scale analysis. An explorational-longitudinal and retrospective study was designed and a total of 36,883 individual match observations were collected on outfield players competing across four consecutive Spanish LaLiga seasons (from 2015/16 to 2018/19), using an optical tracking system (ChyronHego). Soccer players were divided into 3 age groups: young (18-24 years old), middleaged (25-30 years old), and seniors (31-41 years old). Relative total distance (TD/min), distance covered at 21-24 km· h-1 (HIRD/min), and > 24 km· h-1 per minute (VHIRD/min) were analysed; also, the number of efforts at 21-24 km·h-1 (Sp21) and > 24 km·h-1 (Sp24) were taken into consideration. Seasons were divided into four phases (P): P1 (matches 1-10), P2 (11-19), P3 (20-29), and P4 (30-38). The results showed that young players covered significantly greater TD, HIRD and VHIRD than the rest of the players (p < .05) in all season phases. In addition, TD significantly decreased along season phases in all player age group (p < .01). Crucially, young players performed significantly greater numbers of Sp21 and Sp24 than the rest of the players (p < .05) in all season phases. In addition, Sp21 and SP24 significantly decreased in middle-aged (p < .01) and senior players (p < .05) across the seasons. This study demonstrated that players` match running performance decreases with increasing years, especially in high-intensity running distances.